Early Detection of Psychosexual in Adolescent - Putri, Anggi Egliana; Nuryani, Reni; Lindasari, Sri Wulan (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescent psychosexual development is in the genital phase, in this phase there is maturity of sexual function. Adolescence is still learning about exploring new and unfamiliar areas of sexuality, therefore adolescents are vulnerable to the impact of sexual deviations which are included in psychosexual disorders. Early detection is the first step to prevent psychosexual disorders in adolescents. Objective: This research aims to determine the psychosexual conditions t Adolescent psychosexual development is in the genital phase, in this phase there is maturity of sexual function. Adolescence is still learning about exploring new and unfamiliar areas of sexuality, therefore adolescents are vulnerable to the impact of sexual deviations which are included in psychosexual disorders. Early detection is the first step to prevent psychosexual disorders in adolescents. Objective: This research aims to determine the psychosexual conditions that occur in adolescents. This research is a quantitative study employing Univariate data analysis. The study population amounted to 1027 with a sample size of 288 respondents using the Stratified Random Sampling technique. The instrument used is the Bem Sex Inventory (BSRI) to describe gender identity which has been tested for validity and reliability with a Cronbach's alpha of 0.868 and a Likert Scale Instrument to describe sexual orientation which has been tested for validity and reliability with a Cronbach's alpha of 0.702. Data collection techniques were carried out by distributing questionnaires to measure gender identity and sexual orientation. In measuring gender identity, the majority of respondents, 95 people (32.99%) have an androgynous gender identity, 93 respondents (32.29%) have gender undifferentiated, some respondents, 20 male students (6.94%) have masculine and as many as 59 female students (20.49%) have feminine traits, 6 female students (2.08%) have masculine traits and 15 male students (5.21%) have feminine traits. Meanwhile, the results of measuring sexual orientation showed that the majority of students and female students have heterosexual interests, 276 respondents (95.83%) and 12 respondents (4.17%) have non-heterosexual interests. Most respondents have an Androgynous gender identity and a Heterosexual sexual orientation. hat occur in adolescents. Methods: This research is a quantitative study using descriptive research design. The study population amounted to 1027 with a sample size of 288 respondents using the Stratified Random Sampling technique. The instrument used is the Bem Sex Inventory (BSRI) to describe gender identity which has been tested for validity and reliability with a Cronbach's alpha of 0.868 and a Likert Scale Instrument to describe sexual orientation which has been tested for validity and reliability with a Cronbach's alpha of 0.702. Data collection techniques were carried out by distributing questionnaires to measure gender identity and sexual orientation. Results: In measuring gender identity, the majority of respondents, 95 people (32.99%) have an androgynous gender identity, 93 respondents (32.29%) have gender undifferentiated, some respondents, 20 male students (6.94%) have masculine and as many as 59 female students (20.49%) have feminine traits, 6 female students (2.08%) have masculine traits and 15 male students (5.21%) have feminine traits. Meanwhile, the results of measuring sexual orientation showed that the majority of students and female students have heterosexual interests, 276 respondents (95.83%) and 12 respondents (4.17%) have non-heterosexual interests. Conclusion: Most respondents have an Androgynous gender identity and a Heterosexual sexual orientation.